Bioremediation of Agro-Based Pulp Mill Effluent by Microbial Consortium Comprising Autochthonous Bacteria - Virendra Kumar; Purnima Dhall; Rita Kumar; Yogendra Prakash Singh; Anil Kumar (The Scientific World Journal)
Small-scale agro-based pulp and paper mills are characterized as highly polluting industries. These mills use Kraft pulping process for paper manufacturing due to which toxic lignified chemicals are released into the environment. Lack of infrastructure, technical manpower, and research and development facilities restricts these mills to recover these chemicals. Therefore, the chemical oxygen demand (COD) of the emanating stream is quite high. For solving the above problem, four bacteria were isolated from the premises of agro-based pulp and paper mill which were identified as species of Pseudomonas, Bacillus, Pannonibacter, and Ochrobacterum. These bacteria were found capable of reducing COD up to 85%–86.5% in case of back water and 65-66% in case of back water : black liquor (60 : 40), respectively, after acclimatization under optimized conditions (pH 6.8, temperature 35°C, and shaking 200 rpm) when the wastewater was supplemented with nitrogen and phosphorus as trace elements.